Cushing's syndrome due to adrenocorticotropic hormone-secreting pheochromocytoma - G V Chanukya; Manoj Mengade; Babu Reddy (Wolters Kluwer Medknow Publications, 2016)
Adrenocorticotropic hormone (ACTH) producing pheochromocytoma is the rare cause of Cushing's syndrome (CS). Herein, we present a 53-year-old female patient with ectopic ACTH-dependent Cushing's syndrome due to pheochromocytoma. ACTH secreting pheochromocytoma is a rare but important source of ectopic ACTH secretion. Early diagnosis of pheochromocytoma with CS needs a high index of suspicion. The scenario provides clues for a detailed discussion about the pitfalls and diagnostic difficulties in establishing the underlying cause of ACTH-dependent CS. It demonstrates relative contributions of clinical, biochemical, and radiological clues in arriving at the correct underlying cause of CS.